2019
DOI: 10.3171/2017.12.jns171597
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of myelin water fraction changes after mild traumatic brain injury in collegiate contact sports

Abstract: OBJECTIVEMild traumatic brain injury (mTBI) in athletes, including concussion, is increasingly being found to have long-term sequelae. Current imaging techniques have not been able to identify early damage caused by mTBI that is predictive of long-term symptoms or chronic traumatic encephalopathy. In this preliminary feasibility study, the authors investigated the use of an emerging magnetic resonance imaging (MRI) technique, multicomponent driven equilibrium single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 165 publications
(163 reference statements)
0
10
0
2
Order By: Relevance
“…As expected, no statistically robust (i.e., significant after correcting for multiple comparisons using FDR) difference in post-acute white matter microstructure was observed between children with mild TBI and those with OI. The limited finding of reduced microstructure of bilateral thalamic radiation white matter in mild TBI should be interpreted with caution given that it did not survive correction for multiple comparison, although similar reductions have previously been reported in post-acute pediatric mild TBI (Mayer et al., 2012; Myer et al., 2016; Spader et al., 2018). Post-acute diffusion metrics also did not differentially predict PCS in the two injury groups, with the exception of left cingulum hippocampus and thalamic radiation MD values, which only predicted cognitive PCS at 3 months post-injury in children with OI.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As expected, no statistically robust (i.e., significant after correcting for multiple comparisons using FDR) difference in post-acute white matter microstructure was observed between children with mild TBI and those with OI. The limited finding of reduced microstructure of bilateral thalamic radiation white matter in mild TBI should be interpreted with caution given that it did not survive correction for multiple comparison, although similar reductions have previously been reported in post-acute pediatric mild TBI (Mayer et al., 2012; Myer et al., 2016; Spader et al., 2018). Post-acute diffusion metrics also did not differentially predict PCS in the two injury groups, with the exception of left cingulum hippocampus and thalamic radiation MD values, which only predicted cognitive PCS at 3 months post-injury in children with OI.…”
Section: Discussionmentioning
confidence: 63%
“…With few exceptions, most studies have compared children with mild TBI to typically developing children. Some studies have included non-concussed athletes or athletes who participate in noncontact sports (Mustafi et al., 2018; Spader et al., 2018). Less commonly, children with mild TBI have been compared to children with mild extracranial or orthopedic injuries (OI; Babcock et al., 2015; Ewing-Cobbs et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A study on mouse models of mTBI examined progression of white matter pathology and found a pattern of acute myelin loss at 3 days followed by a pattern of remyelination at 1 week and excessive myelination by 6 weeks (Mierzwa, Marion, Sullivan, McDaniel, & Armstrong, 2015). In a recent study, Spader et al (2018) used multicomponent driven equilibrium single pulse observation of T1 and T2, a quantitative myelin imaging technique, to study 27 collegiate athletes. They found that athletes had higher myelin water fraction (MWF), a measure of myelin content, when compared to healthy controls at 72 hours after injury.…”
Section: Interpreting Microstructural Differences At Whole-track and Segment-levelsmentioning
confidence: 99%
“…Na fase crônica após o trauma, há maior consenso, com a maioria dos estudos mostrando redução da FA na substância branca dos pacientes (Nakayama et al, 2006;Sidaros et al, 2008;Xu et al, 2007;Ljungqvist et al, 2011) e aumento das difusividades média, paralela e perpendicular (Ljungqvist et al, 2011). (Spader et al, 2018). Assim, há sólidas evidências sobre a alta sensibilidade dessa técnica à mielinização, com estudos evidenciando significativa redução da fração da água mielínica com a idade (Dean et al, 2016;Dean et al, 2017), em doenças neurodegenerativas como o Alzheimer (Dean et al, 2017) e a esclerose lateral primária (Kolind et al, 2012), e em pacientes com esclerose múltipla (Kolind et al, 2012;Li et al, 2014).…”
Section: Imagem De Tensor De Difusãounclassified
“…Em relação ao TCE, estudos evidenciam uma redução nas primeiras semanas (Wright et al, 2016), com posterior aumento (Wright et al, 2016;Spader et al, 2018). (Does et al, 1998).…”
Section: Imagem De Tensor De Difusãounclassified